Association between Composite Restoration in Anterior Teeth and Secondary Caries - Nurul Syamimi binti Mohd Azlan Sunil1 , Iffat Nasim2 , Revathi Duraisamy3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Composite resin is one of the most commonly used restorative material during the past decade as it providesdesirable esthetics, easy to manipulate and minimal cavity preparation required. Despite numerous benefitsprovided by composites, several clinical studies have reported short longevity and higher rate of failure incomposite restoration. One of the main reasons for failure was due to recurrent or secondary caries. The aimof this study was to evaluate the association between composite restoration in anterior teeth and secondarycaries. This study included patients above 18 years with composite restoration filled anterior teeth whoreported to dental hospital from June 2019 to March 2020. Patients below 18 years, medically compromisedpatients and patients without anterior composite restorations were excluded from the study. A total of around86000 patient records were reviewed and analysed for the inclusion criteria and the following parameterswere extracted; (i) Patient’s gender, (ii) teeth involved, (iii) presence of secondary caries and (iv) typesof restoration. Data was recorded into Microsoft Office Excel (2013) and analysed using SPSS softwareVersion 26.0. Chi-square test was done to find out correlation of presence of secondary caries betweenvariables such as patient’s gender, teeth involved and types of restoration. Significant test level was set atp<0.05. A total of 1062 teeth presented with composite restoration in anterior teeth. 17.6% of compositefilled anteriors presented with secondary caries. Class III restoration had the highest prevalence of secondarycaries (61%) and was found to be statistically significant (p<0.05). Females (18.3%) had higher incidenceof secondary caries than compared to males (16.6%). Maxillary central incisors had the highest presenceof secondary caries (64.2%). Within the limits of this study, it was observed that less number of compositefilled anterior teeth had secondary caries and females presented with more number of anterior compositerestoration with secondary caries compared to males. Class III restorations demonstrated higher presence ofsecondary caries than other types of restoration.